Tradução, adaptação transcultural e análise psicométrica do Asthma Self-Management Questionnaire para a população brasileira - Lopes, Lenice Daiane da Costa (2024)
Introduction: Given the lack of health measurement instruments in the context of asthma selfmanagement, it is necessary to develop tools that can assist Brazilians diagnosed with asthma in managing their own health condition. Objectives: This study aimed to translate, crossculturally adapt and assess the measurement properties of the ASMQ for the Brazilian population. Methods: This is an exploratory and psychometric study approved by the CEP of UFRN, under opinion number 6.062.022. The statistical software SPSS (22.0) and JASP (16.4) were used, attributing a significance level of 5%. In this study, international guidelines were used as a guide for the preparation and execution of the eight stages of the study. For the translation phase of the instrument, the Delphi Technique was used, through the Multidisciplinary Committee of Experts. And, for the cross-cultural adaptation, a pre-test stage was carried out, through a questionnaire applied to subjects similar to the eligibility criteria. In the psychometric analysis of the tool, the properties of the construct were measured using the ASMQ-Brazil, ACT and AQLQ(S). The content validity and reliability of the instrument were also analyzed. Results: An IVC > 0.80 was found for all items and adequate internal consistency (α = 0.762). In addition, the KMO test had a result of 0.756 and Bartlett's sphericity test found a χ² (chi-square) value of 257.903 with 120 degrees of freedom and significance of p < 0.001, which indicates adequate data adjustment. Finally, this study found mean values for the raw score of 8.98 ± 2.95 points and for the transformed score of 56.17 ± 18.45 points. Correlation tests demonstrated a very weak correlation with no statistical significance between ASMQ-Brazil and ACT (r = 0.043 and p = 0.704) and between ASMQ-Brazil and AQLQ(S) (r = 0.043 and p = 0.704), respectively. Conclusion: ASMQ-Brazil is a valid, reliable and accessible health measurement instrument for assessing asthma self-management in the Brazilian population.